IMPROVEMENT OF SYSTEM OF COMPENSATION OF NPR OF HIGHER EDUCATION INSTITUTION - Andrey E. Shklyaev; Valentina V. Pavlova (Статистика и экономика, 2016)
The article is devoted to the problem of formation of effective system of remuneration of scientific and pedagogical staff of the University. The characteristic of different systems of remuneration of teachers of Russian higher educational institutions. Formulated some proposals for improving the effectiveness of the remuneration system of the NRP of the University. The suggested remuneration system makes it possible to relate the amount of salary of each individual teacher’s or employee’s performance with educational institutions in General and his personal labour contribution in particular.